Happiness in school organizations: the role of leadership (a scoping review) - Vale, Andreia; Ribeiro, Luísa Mota; Alves, José Matias (Frontiers in Education, 2025)
IntroductionEducational organizations are increasingly concerned with students’ well-being and happiness in order to improve the quality of learning and promote the sustainability of teaching. Literature has shown that teacher happiness is related to students’ happiness and contributes to better academic performance, greater motivation and psychological well-being. In an increasingly uncertain, unpredictable and competitive school organizational reality, it is important that top and middle leaders recognize the significant power they have to influence the members of their organization, whether positively or negatively. The practice of successful leadership in a school context is essential to promote positive environments and inspire confidence in teachers, technicians, educational assistants and students.ObjectivesMap the existing literature to understand the role of leadership in promoting student and teacher happiness in school environments.MethodologyA Scoping Review was carried out, following the guidelines proposed by PRISMA-ScR (Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews), to ensure methodological validity and reliability. The research was carried out in five scientific databases, considering the defined eligibility criteria.Results and discussionA total of 17 articles were analyzed, as they met the established inclusion criteria. It was found that school happiness is promoted by factors such as a sense of belonging, interpersonal relationships, academic self-efficacy and teachers’ personal and pedagogical skills. Regarding the analysis of the role of leadership, it was possible to perceive that there are several styles that are related to happiness in the school environment.ConclusionThis review showed that the combination of leadership styles is fundamental, since there is no single leadership style that is considered effective for all contexts and situations, and it may vary depending on the school environment and circumstances.